Characterizing bonding patterns in diradicals and triradicals by density-based wave function analysis: a uniform approach - Orms, Natalie; Rehn, Dirk R.; Dreuw, Andreas; Krylov, Anna I. (Journal of chemical theory and computation, 2018)
Density-based wave function analysis enables unambiguous comparisons of the electronic structure computed by different methods and removes ambiguity of orbital choices. We use this tool to investigate the performance of different spin-flip methods for several prototypical diradicals and triradicals. In contrast to previous calibration studies that focused on energy gaps between high- and low spin-states, we focus on the properties of the underlying wave functions, such as the number of effectively unpaired electrons. Comparison of different density functional and wave function theory results provides insight into the performance of the different methods when applied to strongly correlated systems such as polyradicals. We show that canonical molecular orbitals for species like large copper-containing diradicals fail to correctly represent the underlying electronic structure due to highly non-Koopmans character, while density-based analysis of the same wave function delivers a clear picture of the bonding pattern.
Published: December 21, 2017
Gesehen am 24.03.2020